Nonlinear Vibrations and the Wave Equation - Haraux, Alain (SpringerBriefs in Mathematics,, 2018)
This book gathers the revised lecture notes from a seminar course offered at the Federal University of Rio de Janeiro in 1986, then in Tokyo in 1987. An additional chapter has been added to reflect more recent advances in the field.